Molecular analysis of the Ccr4-Not deadenylase: relevance to human disease - Airhihen, Blessing (2017)
In eukaryotes, the removal of the poly (A) tail of cytoplasmic mRNA (deadenylation) is a crucial step in post-transcriptional gene regulation. A major enzyme involved in regulated mRNA deadenylation is the Ccr4-Not deadenylase, which contains two catalytic subunits: the Caf1 and Ccr4 ribonucleases. For both enzymes, two Mg2+ ions are required in the active site for activity. These enzymes in addition to six other non-catalytic subunits of the Ccr4-Not complex are possible drug targets in diseases such as metastatic cancer, osteoporosis and obesity. To facilitate the discovery, development and characterisation of small drug-like inhibitors of these enzymes, a biochemical approach was used. First, we investigated the biochemical characteristics of the highly similar CNOT6 and CNOT6L enzymes. Next, we evaluated two biochemical assays for characterisation of Ccr4-Not catalytic subunits and evaluation of N-hydroxyimide inhibitors of CNOT7. A chemiluminescence-based detection assay of AMP was used as the basis of a method and thermal shift assays were also used to characterize binding of compounds to deadenylase enzymes. In addition, cell based assays were used to study interactions between BTG2 variants and CNOT7 and CNOT8 in lymphoma. Our findings demonstrate that the CNOT6 and CNOT6L though highly similar, display different biochemical characteristics in vitro. The deadenylase activity of CNOT6 was higher compared to CNOT6L. The results also indicate that AMP detection is a highly sensitive assay that can be used as a secondary assay to the previously developed substrate-based assay for compound screening and IC50 determination. We conclude that thermal shift assays can be used to determine the binding mode of inhibitory compounds, specifically regarding the presence of the Mg2+ ions in the active site. Finally, we identified BTG2 variants that potentially regulate mRNA abundance in lymphoma via interaction with the Ccr4-Not deadenylase.